Analisis Akuntabilitas dalam Pengelolaan Keuangan Lembang Sereale - Lipa Banne; Dina Ramba; Yohanis Lotong Ta’dung (Moneter : Jurnal Ekonomi dan Keuangan, 2023)
This study aims to determine accountability in the financial management of Lembang sereale. This type of research uses qualitative research where the author observes, interviews, records, and analyzes the object of research, data obtained through interviews and documents obtained in connection with the problem studied. The results of this study show that Lembang's financial accountability is good as seen from the Minister of Home Affairs regulation no. 20 of 2018 starting from the process of planning, implementation, administration, reporting and accountability has been implemented properly.